Debt and the Miracle: On the Economy of Grace and Conversion in Berceo’s Milagros de Nuestra Señora - Pinet, Simone (Revista Canadiense de Estudios Hispánicos, 2023)
This article reads two of Gonzalo de Berceo’s Miracles of Our Lady, tracing how different economic operations find a vocabulary in moral words and concepts that open up to economic metaphorization and become ambiguous and polysemic. The analysis proposes that Miracle X “The Two Brothers,” and Miracle XXIII “The Merchant of Byzantium,” both structured on debt, present a particular idea of conversion.